Challenges and Countermeasures of Banking Risk Management in Digital Transformation: Case study of state-owned commercial banks in China - Li Sijie (SHS Web of Conferences)
In the digital economy era, China’s state-owned commercial banks are undergoing a profound digital transformation. This transformation involves not only technological upgrades but also a complete reshaping of business concepts, organizational structures, and business processes. However, while digitalization brings convenience, it also brings new challenges to risk management in the banking industry, such as data security, privacy protection, technology risks, and compliance issues. Through case studies, this study examines the risk management challenges faced by Chinese state-owned commercial banks in the process of digital transformation and proposes corresponding countermeasure strategies. The main countermeasures include strengthening data governance and privacy protection mechanisms, introducing advanced technologies such as artificial intelligence and big data to improve the accuracy and efficiency of risk identification, cultivating composite risk management talents, and promoting the deep integration of technology and business within banks. In addition, the success of digital transformation requires policy guidance from regulators and collaborative efforts within and outside the industry to build a safe, efficient, and sustainable financial ecosystem jointly.